Comprehensive Metabolomic and Transcriptomic Analysis Revealed the Molecular Basis of the Effects of Different Refrigeration Durations on the Metabolism of Agaricus bisporus Cultivation Spawn - Zhixin Cai; Zhiheng Zeng; Wenzhi Chen; Zhongjie Guo; Huiqing Zheng; Yuanping Lu; Hui Zeng; Meiyuan Chen (Journal of Fungi)
Agaricus bisporus is popular worldwide because of its high nutritional value and low cost. Low-temperature storage is a common storage method used for the production and sales of A. bisporus cultivation spawn, but few studies have focused on the physiological and biochemical mechanisms associated with low-temperature storage of A. bisporus cultivation spawn. In this study, we examined A. bisporus spawn samples stored for different refrigeration periods (0, 20, 40, 60, 80, and 100 days), measured changes in the activities of four key extracellular enzymes and performed transcriptomic and metabolomic analyses. The results of the enzymatic assays revealed that the activities of carboxymethyl cellulase (CMCase), amylase, and acid protease initially decreased before increasing, whereas laccase activity showed the opposite trend. This pattern may represent an energy supply mechanism adopted by A. bisporus to cope with low temperatures, where extracellular enzymes indirectly influence survival by mediating substrate decomposition. Further correlation analysis on the basis of CMCase activity changes revealed 148 carboxymethyl cellulase-correlated metabolites (CCMs) and 514 carboxymethyl cellulase-correlated genes (CCGs) (p ≤ 0.05), and significance was determined at FDR < 0.05 with a fold change > 1.5. Among these, 56.08% of the CCMs and 63.04% of the CCGs presented positive correlations with CMCase activity, whereas 43.92% and 36.96% presented negative correlations, respectively. Integrated multiomics analysis revealed significant variations in metabolic flux and gene expression across different storage durations. Two CCMs (ketoleucine and 3-methyl-2-oxovaleric acid) gradually decreased in expression, whereas two CCGs (AbbBCAT and AbbAACS) increased in expression. This study provides novel insights into the molecular adaptation of A. bisporus spawn to refrigeration, highlighting the importance of branched-chain amino acid metabolism in the cold stress response and storage stability.